Exchange rate movements and fundamentals: Impact of oil prices and the People's Republic of China's growth - Hongyi Chen; Shuo Cao (Asian Development Bank Institute (ADBI), 2019)
This paper identifies five factors that can capture 95% of the variance across 39 US dollar exchange rates based on the principal component method. A time-varying parameter factor-augmented vector autoregressive (TVP-FAVAR) model is used to analyze the determinants of movements in these exchange rates, revealing that their impact on global oil prices and the People's Republic of China's growth has increased significantly since 2008. In particular, the variance of US dollar exchange rates has mainly been driven by these two shocks in recent years. The impact of monetary policy shocks on the currency pairs is comparatively small.
Keywords: C11; C22; F31; G12; 330; exchange rates; commodity prices; People's Republic of China's growth; monetary policy; factor model; TVP-FAVAR; Bayesian methods